PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI BADAN USAHA MILIK DESA (BUMDES) ARYA KAMUNING DI DESA WISATA KADUELA KABUPATEN KUNINGAN - Andien Novicka Zaelani Putri; Sutarjo Sutarjo; Ratna Sari Dewi (Comm-Edu (Community Education Journal), 2026)
Community economic empowerment is an important strategy in improving welfare and independence based on local potential. Village-Owned Enterprises (BUMDes) function as village economic institutions that manage resources and develop productive community businesses. In the context of tourism villages, BUMDes play a strategic role in integrating tourism potential with community economic activities. However, the implementation of empowerment through BUMDes still faces challenges, particularly in community participation, equitable distribution of benefits, and management quality. In addition, studies that specifically examine the process of community economic empowerment through BUMDes in tourism village contexts remain limited. This study aims to analyze the process of community economic empowerment through BUMDes Arya Kamuning in Kaduela Tourism Village, Kuningan Regency, as well as to identify supporting and inhibiting factors and the outcomes achieved. This research uses a qualitative approach with a case study method through interviews, observations, and documentation involving seven informants. The results show that the empowerment process is carried out through stages of awareness, capacity building, empowerment, and independence. BUMDes plays a role in creating business opportunities, increasing income, and strengthening community skills. Supporting factors include tourism potential and village government support, while inhibiting factors include limited human resources and fluctuating tourist visits. Overall, empowerment has a positive impact, although institutional strengthening and increased community participation are still needed.